Bronchial inflammation and bacterial load in stable COPD is associated with TLR4 overexpression. Issue 5 (23rd May 2017) - Di Stefano, Antonino; Ricciardolo, Fabio L.M.; Caramori, Gaetano; Adcock, Ian M.; Chung, Kian Fan; Barnes, Peter J.; Brun, Paola; Leonardi, Andrea; Andò, Filippo; Vallese, Davide; Gnemmi, Isabella; Righi, Luisella; et al.
Toll-like receptors (TLRs) and nucleotide-binding oligomerisation domain (NOD)-like receptors (NLRs) are two major forms of innate immune sensors but their role in the immunopathology of stable chronic obstructive pulmonary disease (COPD) is incompletely studied. Our objective here was to investigate TLR and NLR signalling pathways in the bronchial mucosa in stable COPD. Using immunohistochemistry, the expression levels of TLR2, TLR4, TLR9, NOD1, NOD2, CD14, myeloid differentiation primary response gene 88 (MyD88), Toll-interleukin-1 receptor domain-containing adaptor protein (TIRAP), and the interleukin-1 receptor-associated kinases phospho-IRAK1 and IRAK4 were measured in the bronchial mucosa of subjects with stable COPD of different severity (n=34), control smokers (n=12) and nonsmokers (n=12). The bronchial bacterial load of Pseudomonas aeruginosa, Haemophilus influenzae, Moraxella catarrhalis and Streptococcus pneumoniae was measured by quantitative real-time PCR. TLR4 and NOD1 expression was increased in the bronchial mucosa of patients with severe/very severe stable COPD compared with control subjects. TLR4 bronchial epithelial expression correlated positively with CD4 + and CD8 + cells and airflow obstruction. NOD1 expression correlated with CD8 + cells. The bronchial load of P. aeruginosa was directly correlated, but H. influenzae inversely correlated, with the degree of airflow obstruction. Bacterial load did not correlate with inflammatory cells. Bronchial epithelial overexpression of TLR4 and NOD1 in severe/very severe stable COPD, associated with increased bronchial inflammation and P. aeruginosa bacterial load, may play a role in the pathogenesis of COPD. Inflammation, bacterial load and active antibacterial immune response involving TLR4 and NOD1 in stable COPD http://ow.ly/S1fp308qcwp